Commercial straight-deck trailer vibration and microclimate conditions during market-weight pig transport during summer - Alambarrio, Daniela A.; Morris, Benjamin K.; Davis, R. Benjamin; Turner, Kari K.; Motsinger, Laura A.; O’Quinn, Travis G.; Gonzalez, John M. (Frontiers in Animal Science, 2022)
The objective of this study was to collect and quantify three-axis acceleration data from six locations within commercial pig transport trailers during summer. Two trucks with straight-deck trailers transporting two loads per day were observed for five consecutive days (N = 20). Accelerometers were placed under trailers’ top and bottom decks’ (DEC) floors, in the center, of three sections (SEC; fore, middle, aft). Data from each trailer section were processed to calculate z- and x-y-axis root-mean-squared (RMS) and vibration dose value (VDV) during loading, transport, and unloading. There were no DEC × SEC interactions or SEC main effects for z-axis RMS or VDV during any transportation stages (P > 0.06). The bottom deck had greater x-y axis RMS than the top deck during all transportation stages (P < 0.01). The bottom deck had greater x-y-axis VDV than the top deck during loading and transport (P < 0.03), but no difference (P = 0.52) during unloading. The bottom deck had greater z-axis RMS and VDV than the top deck during loading and transport (P < 0.01), but there were no differences during unloading (P > 0.07). There were no SEC effects for x-y- and z-axis RMS and VDV during all transportation stages (P > 0.06). Acceleration values were compared to exposure action values (EAV; injury possible) and exposure limit values (ELV; injury likely) vibrations thresholds. Over the five observation days during all transport stages, a greater percentage of compartments violated both RMS and VDV thresholds in the x-y orientation (average 90%) more than the z-oritentation (average 76%). Overall, these data indicate straight-deck trailer bottom decks experience greater three-axis vibrations than top decks and pigs may experience discomfort during transportation that could contribute to fatigue or the non-ambulatory condition.